Long-term trends in the use of a protected area by small cetaceans in relation to changes in population status - Barbara Cheney; Ross Corkrey; John W. Durban; Kate Grellier; Philip S. Hammond; Valentina Islas-Villanueva; Vincent M. Janik; Susan M. Lusseau; Kim M. Parsons; Nicola J. Quick; Ben Wilson; Paul M. Thompson (Global Ecology and Conservation, 2014)
The requirement to monitor listed species in European designated sites is challenging for long-lived mobile species that only temporarily occupy protected areas. We use a 21 year time series of bottlenose dolphin photo-identification data to assess trends in abundance and conservation status within a Special Area of Conservation (SAC) in Scotland. Mark–recapture methods were used to estimate annual abundance within the SAC from 1990 to 2010. A Bayesian mark–recapture model with a state-space approach was used to estimate overall population trends using data collected across the populations’ range. Despite inter-annual variability in the number of dolphins within the SAC, there was a >99% probability that the wider population was stable or increasing. Results indicate that use of the SAC by the wider population has declined. This is the first evidence of long-term trends in the use of an EU protected area by small cetaceans in relation to changes in overall population status. Our results highlight the importance of adapting the survey protocols used in long-term photo-identification studies to maintain high capture probabilities and minimise sampling heterogeneity. Crucially, these data demonstrate the value of collecting data from the wider population to assess the success of protected areas designated for mobile predators. Keywords: Abundance, Bayesian, Bottlenose dolphin, Mark–recapture, Photo-identification, Special Area of Conservation